STUDI PERILAKU SATPAM TERHADAP PENANGGULANGAN KEBAKARAN DI INSTANSI X - Danang Alfriandi Legowo; Bina Kurniawan; Besar Tirto Husodo (Jurnal Kesehatan Masyarakat (Undip), 2015)
According to International Labor Organization (ILO), every year there are 2 million deaths all over the world related to work. One of caused by fire. Fire is an uncontrolled flame that means beyond the capability and human wish. Fires ini institution X and the absence of security in doing fire-fighting led to one of the rooms burned. The purpose of this research to study the behavior of security against fire prevention in institution X. This research is a descriptive qualitative research with indepth interview. The subjects of this research were 5 people as akey informants and 2 people as a triangulation informants. The results showed key informants already know the definition of a fire, the cause of fire and using a fire extinguisher. Attitude key informants already know how to use the fire extinguisher. Availability of fire prevention facility such as fire extinguishers. Key informants had never been trained fire by institution X and supervision provided by the informant triangulation is a way of making a form to be filled every 2 hours. Key informants behavior towards fire prevention already know how to use fire extinguisher, have the awareness to quickly extinguish the fire and fire-fighting facilities are available fire extinguisher. Institution X need to provide fire training to the key informants to increase the capacity and responsiveness against fire prevention.